Eco-epidemiological study reveals the importance of Triatoma dimidiata in the Trypanosoma cruzi transmission, in a municipality certified without transmission by Rhodnius prolixus in Colombia (2020)
Boyaca department is an endemic area for Chagas disease in Colombia, where 24 of its municipalities have been certified by the PAHO with interruption of Trypanosoma cruzi transmission by R. prolixus. However, the presence of secondary vectors, represent a risk of parasite transmission for citizens and a challenge for the health care institutions. The aim of this work was to investigate eco-epidemiological features of Chagas disease in the municipality of Socota (Boyaca), in order to improve control and surveillance strategies. To understand the transmission dynamics of T. cruzi in this area, we designed a comprehensive, multi-faceted study including: (i) entomological survey in five villages (La Vega, Comaita, Chusvita, Guaquira and Pueblo Nuevo), (ii) blood meal source determination, (iii) T. cruzi infection rate in collected triatomines, (iv) identification of circulating T. cruzi genotypes, (v) serological determination of T. cruzi infection in domestic dogs; and (vi) evaluation of infection in synanthropic mammals. A total of 90 T. dimidiata were collected, of which 73.3% (66/90) and 24.4% (22/90) were collected inside dwellings and peridomestic areas, respectively, while the rest (2/90) in Chusvita Elementary School. T. cruzi infection was evidenced in 40% (36/90) of triatomine bugs using PCR analyses, in which only DTU I was found, and TcI Dom was the most distributed. Blood-meal analysis showed that T. dimidiata only fed of humans. Seroprevalence in domestic dogs was 4.6% (3/66), while that two Didelphis marsupialis captured showed no infection. In conclusion, the high dispersion and colonization of T. dimidiata shown in this municipality, along the high rate of T. cruzi (TcI) infection and its anthropophilic behavior constitute a risk situation for Chagas disease transmission in this municipality certified without R. prolixus. The epidemiological implications of these findings are herein discussed. © 2020 The Authors